Crab burrows as preferential flow conduits for groundwater flow and transport in salt marshes: A modeling study - Xiao, Kai; Wilson, Alicia M.; Li, Hailong; Ryan, Carolyn (Advances in water resources, 2019)
•Porewater salinity differs between macropores and the adjacent sediment matrix.•Crab burrows can significantly increase the intensity and duration of soil aeration.•Crab burrows can provide an efficient pathway for salt transport in coastal wetlands.•Crab burrows may limit the development of seepage faces in salt marshes. Crab burrows can act as preferential flow conduits for pore water-surface water interactions in salt marshes, but the effect of preferential flow on subsurface transport in these tidally-influenced systems is not fully understood. We used numerical models based on salt marshes of North Inlet, South Carolina, to investigate the impacts of crab burrows on porewater salinity. This modeling effort was inspired by field results from North Inlet, where prior field studies that used a combination of tension samplers and passive diffusion samplers measure salinity in crab burrows and in the adjacent sediment matrix found that the minimum salinity (28 PSU) reported by the tension samplers was larger than the maximum salinity (26 PSU) reported by passive diffusion samplers. Two kinds of numerical models were developed to investigate the effect of crab burrows on tidally-driven groundwater flow and salt transport. In the equivalent-continuum model (ECM), crab burrows were included via a shallow surface layer with hydraulic properties representing a bulk average of sediment matrix and crab burrow properties. In the preferential flow model (PFM), an independent high-permeability material was embedded in the surface muddy layer to explicitly simulate preferential flow conduits. The simulated results showed that both models can depict the effect of crab burrow on soil saturation and salt transport in salt marshes. The presence of crab burrows can greatly increase tidally-driven water exchange, improve the intensity and duration of soil aeration and enhance salt transport in salt marshes. The effect of crab burrows on groundwater flow and salt transport varied spatially from the creek bank to marsh interior. PFM models demonstrated that salinity is likely to differ between crab burrows and the sediment matrix, which supports observed differences in results between tension samplers and passive diffusion samplers. These findings may have important implications for practical pore water sampling and hydrochemical investigation in coastal wetlands.